Factor structure and psychometric properties of the affective lability scale-short form in Chinese adolescents - Xu, Shuyin; Chen, Yafei; Li, Yunjing; Yang, Siqi; Lu, Yimei; Li, Liang; Huang, Mei; Ma, Mohan; Ou, Wenwen; Lv, Guanyi; Zhao, Xiaotian; Qin, Yaqi; et al. (Frontiers in Psychiatry, 2022)
Objective: Previous studies on the reliability and validity of the Affective Lability Scale short-form (ALS-SF) have only been evaluated in adults, which may not be able to generalize to the adolescent population. We aimed to examine the factor structure, the reliability and validity of ALS-SF among Chinese adolescents and construct an adolescent form of ALS (ALS-AF). Methods: A total of 1439 middle school students were investigated with a broad survey including ALS-SF, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-item (GAD-7), Connor-Davidson Resilience Scale 10-item (CD‐RISC-10) and non-suicidal self-injury (NSSI) behavior self-report. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to investigate the structural validity of ALS-SF and construct ALS-AF. Cronbach’s α was used to assess the internal consistency and reliability of the scale. Factor loading, Average Variance Extracted (AVE) and Composite Reliability (CR) were applied to measure the convergent validity and divergent validity. Besides, Correlation and regression analyses were used to explore the relationship between affective liability and depression, anxiety, NSSI and resilience. Results: Factor analysis failed to support the original three-factor model of 18-item ALS-SF and confirmed the three-factor model of 15-item ALS-AF. The ALS-AF showed good internal consistency as well as strong convergent and discriminative validity. Besides, ALS-AF was positively correlated with PHQ-9, GAD-7 and self-harm, and was negatively associated with resilience. Conclusion: Our study shows that the ALS-AF has good reliability and validity for testing affective lability in Chinese adolescents.